Cambodia : Staff Report for the 2001 Article IV Consultation and Fourth Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2002)
This paper assesses Cambodia's 2001 Article IV Consultation and Fourth Review Under the Poverty Reduction Growth Facility (PRGF). The PRGF-supported program approved in October 1999 aims at sustaining economic growth, reducing poverty, and accelerating economic reconstruction. In the first two years of the program, significant progress has been made. Priority structural policies for the third year of the PRGF arrangement focus on improving tax and customs administration, enhancing expenditure management, and continuing the bank restructuring program-including reform of the publicly owned Foreign Trade Bank.